‘Getting Going’ – Research by Design - Morrison, Andrew; Sevaldson, Birger (FormAkademisk, 2010)
Research by Design is the theme of this first special guest edited issue of FORMakademisk. In this issue we look into a growing domain of design research that takes up relations between practice and theory that are pertinent for inquiry in the interdisciplinary approaches and frameworks that are often central to research in design (Rust et al. 2005). As the articles gathered here show, this is research than spans a range of established and emerging areas and their methods and analyses. The articles indicate how far design research has moved from earlier locations in craft traditions and historical analyses and characterisations and perspectives lodged in industrial design. These views do still matter, but they are now part of the changing profession of design and a burgeoning body of international research.